AB0423 NEUROPSYCHIATRIC OUTCOME OF CHILDREN BORN TO WOMEN WITH SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) WOMEN AND EXPOSED IN UTERO TO AZATHIOPRINE: A CASE-CONTROL STUDY. (2nd June 2020) - Lazzaroni, M. G.; Crisafulli, F.; Debeni, I.; Nalli, C.; Andreoli, L.; Galli, J.; Merlini, A.; Fazzi, E.; Franceschini, F.; Tincani, A.
Abstract : Background: A possible increase in neurodevelopmental (ND) and learning disorders (LD) in the offspring of mothers affected by SLE have been suggested in some studies, along with the identification of different possible risk factors. Azathioprine (AZA) is commonly used during pregnancy, based on its non-teratogenicity and extended experience in women with different diseases. However, a few small studies suggested an association between in utero exposure to AZA and possible increased frequency of ND/LD in children, indirectly derived from increased request of supportive educational services. Objectives: To evaluate the medium-long term outcome in terms of ND/LD in children of school age (≥6 years) born to SLE women treated with AZA during pregnancy, as compared to that of children born to SLE mothers not treated with AZA during pregnancy. Methods: Data from our Pregnancy Clinic registry were collected for prospectively followed pregnancies of SLE women treated with AZA (cases) and compared to pregnancies of SLE women not treated with AZA (controls), that were matched for age at pregnancy, presence of renal involvement and aPL positivity. SLE patients (cases and controls) were interviewed by phone to collect data about their children, focusing on the presence of ND/LD certified by Neuropsychiatrists. Results: Data were collected for 14 SLE mothers in the AZA group and 31 in the control group, with similar age at pregnancy (30.3±5.21 vs 31.4±4.70 years, p:0.45) and frequency of renal involvement (50.0% vs 44.1%, p:0.77), aPL positivity (33.3% vs 29.4%, p:0.76) and anti-Ro/SSA positivity (27.8% vs. 26.5%, p:0.55). A SLE flare during pregnancy was more frequently recorded in the AZA group (27.8% vs. 2.94%, p:0.02). Other medications included HCQ (55.6% vs. 70.6%, p:0.36) and corticosteroids (100% vs 79.4%, p:0.08). We collected data for 18 children in the AZA group and 34 children in the control group, that had a similar mean age at the time of the interview (12.7±4.80 vs. 12.9±5.61 years, p:0.91). The two groups had also similar gestational age (37.4±2.20 weeks vs. 38.0±1.29 weeks, p:0.23), birth weight (3003±433 g vs 3011±453 g, p:0.95) and rate of male sex (61.1% vs 44.1%, p:0.38). We recorded similar frequency of ND/LD in the two groups. In particular, a ND was present in 2/18 (11.1%) of children exposed to AZA vs. 2/34 (5.88%) in the control group (p:0.60). A LD was present in 1/18 cases (5.56%) and 6/34 controls (17.6%) (p:0.40). Conclusion: The medium-long term outcome of children born to SLE mothers in the whole cohort was characterized by the presence of ND in 4/54 (7.69%) and LD in 7/52 (13.5%). ND/LD do not seem to be related to in utero exposure to AZA. Disclosure of Interests: None declared